PROPOSTA DE INTEGRAÇÃO DE MODELOS DE GESTÃO NA ÁREA DE EXPLORAÇÃO E PRODUÇÃO DE PETROLEO: estudo de caso em um ativo de produção de uma unidade de negócio de empresa de petróleo - Luiz, Monir Raggio (2005)
This study has as mark to present a proposal of integration of the models of Environmental Administration, through the requirements of the norm ISO 14001; administration of the Health and Safety of the Work, through the requirements of the norm BS 8800; the corporate guidelines in Safety's areas, Environment and Health of the researched company, being taken as reference the Criteria of Excellence of the Model of the National Prize of the Quality - PNQ 2004. Starting from the analysis of the existent administration models in the Assets of Production of Marlim Leste (ATP-MLL) of the Unit of Business of Rio de Janeiro (UN-RIO) of the area of Exploration & Production of the South-southeast (E&P-SSE) of the company Brazilian Petroleum (PETROBRAS S.A) the objective of the research is to discuss a proposal of integration of the referred Administration models. To formulate the integration proposal the requirements common of each model they are characterized, occurring the correlation among the same ones seeking its consolidation and integration. The results obtained in the extent of the Asset of Production researched were shown positive under several aspects, which are: the possibility of a clearer vision, integrated and systemic of the business; reduction of the amount of evaluations and auditing with the reduction of the costs, and, consequently, the improvement of the results, guaranteeing larger sustainability to the business.